Fundamentals of financial management - Brigham, Eugene F., 1930-; Houston, Joel F. (Mason, Ohio : South-Western Cengage Learning, 2013)
With the same contemporary approach and dynamic examples that made previous editions so popular, this fully revised thirteenth edition of FUNDAMENTALS OF FINANCIAL MANAGEMENT continues to provide students with a focused understanding of today's corporate finance and financial management.
Thomson One access code card inserted to provide access to online resources: current and past company data, financial analyst data and forecasts, SEC disclosure statements, etc.
Includes bibliographical references and index.
AAL
Keywords: Corporations -- Finance; Corporations -- Finance -- Problems, exercises, etc; Business enterprises -- United States -- Finance; Business enterprises -- United States -- Finance -- Problems, exercises, etc; Finance